Endothelial Progenitor Cells Produced From Human Pluripotent Stem Cells by a Synergistic Combination of Cytokines, Small Compounds, and Serum-Free Medium - Farkas, Simon; Simara, Pavel; Rehakova, Daniela; Veverkova, Lenka; Koutna, Irena (Frontiers in Cell and Developmental Biology, 2020)
Human pluripotent stem cells (hPSCs) are a promising source of autologous endothelial progenitor cells (EPCs) which can be used for a treatment of vascular diseases. However this kind of treatment requires high amount of EPCs. Therefore highly efficient, robust and easily reproducible differentiation protocol is necessary. We present serum free differentiation protocol that utilizes novel synergy of powerful differentiation effectors. Our protocol follows proper physiological pathway by differentiating EPCs from hPSCs in three phases that mimic in vivo embryonic vascular development. Specifically hPSCs are differentiated into (i) primitive streak which is subsequently turned into (ii) mesoderm that finally differentiates into (iii) EPCs. This differentiation process yields up to 15 differentiated cells per 1 seeded hPSC in 5 days. EPCs constitute up to 97% of these derived cells. The experiments were performed on human embryonic stem cell line H9 and 6 human induced pluripotent stem cell lines generated in our laboratory. Therefore robustness was verified on high amount of hPSC lines. Some of the previously established protocols were also adapted and compared to our synergistic three phase protocol. Better efficiency and lesser variability were observed for our differentiation protocol in comparison to other tested protocols. Furthermore, EPCs derived from hPSCs by our protocol expressed high proliferative potential EPC marker CD157 on their surface in addition to standard EPC surface markers CD31, CD144, CD34, KDR and CXCR 4. Presented protocol enables efficient fully defined production of autologous endothelial progenitors for research and clinical application.